Anti-Candida sp. activity of Astronium urundeuva derivatives free and loaded into a nanostructured lipid system - Bonifácio, Bruna Vidal [UNESP]; Carvalho, Flávio Alexandre [UNESP]; de Oliveira Mota, Luiza [UNESP]; da Silva, Patrícia Bento [UNESP]; de Souza, Leonardo Perez [UNESP]; Vilegas, Wagner [UNESP]; Chorilli, Marlus [UNESP]; dos Santos, André Gonzaga [UNESP]; Bauab, Taís Maria [UNESP] (Springer Nature, 2024)
Infections caused by Candida species increased, as well as species resistant to the most conventional antimicrobials. Thus, the search for new natural sources of antimicrobials without adverse effects also increased. In this case, Astronium urundeuva Engl., a medicinal plant with several pharmacological activities, including antifungal activity, emerges as a source of antifungal compounds. Here, we evaluated the antifungal activity of A. urundeuva and its derivatives free or loaded into a nanostructured lipid system and combination studies against Candida species. A. urundeuva component's purification and identification were performed through chromatographic and spectroscopic techniques, respectively. The major components identified were gallic acid (1), methyl gallate (2), ethyl gallate (3), and 1,2,3,4,6-penta-O-galoyl-β-D-glucose (PGG) (4). A. urundeuva extract, its aqueous fraction, and PGG (4) exhibited the same MIC values between 0.2 and 62.5 µg/mL against Candida species being classified as significant activity, while the amphotericin B MIC was 0.1–1.2 µg/mL. Combination assay demonstrated that may occur synergism (0.37) between gallic acid (1) x methyl gallate (2). Thus, the results demonstrated as PGG (4) much as the gallic acid (1) x methyl gallate (2) combined might be the main responsible for the antifungal activity against Candida species, mainly Candida glabrata ATCC 2001 and that the tested nanostructured system maintained the antifungal activity. Through the antifungal activity of the extract and purified compounds, the extract may be employed in the development of antifungal herbal medicine, because its purification process is simple and greener than pure compounds.
Keywords: Antifungal activity; Candida albicans; Candida glabrata; Ethyl gallate; PGG; Tannins